Marie kondo's kurashi at home eaudiobook How to organize your space and achieve your ideal life. - Kondo, Marie (Random House Audio, 2022)
Transform your home into a haven of calm and achieve your ideal lifestyle with this inspirational guide, from the Netflix star and #1 bestselling author of The Life-Changing Magic of Tidying Up .   Inspired by the Japanese concept of kurashi, or “way of life,” Kurashi at Home invites you to visualize your best life from the moment you wake up until the end of each day. By applying Marie Kondo's time-tested query —“ Does it spark joy?”—to your mindset and behaviors, you are invited to take an even more holistic and personal approach to curating your environment by imagining what your life could look like full of connection and free from any limitations. This ideal vision then becomes a touchpoint that helps you make conscious, mindful choices—from how you use every corner of your living space to how you take advantage of every moment.   At its core, the KonMari philosophy focuses not on what to get rid of, but on what sparks joy in your life. In this inspirational guide, Kondo's unique suggestions empower you to embrace what you love about your life and then reflect it in your home, activities, and relationships, like creating a calm nook for working, scheduling weekly get-togethers with family or friends, or having relaxing nighttime rituals that promote a restful sleep.   Your newfound clarity will inspire you to clear out the unneeded clutter so you can appreciate the inviting spaces, treasured belongings, and peaceful moments that remain. *Includes a downloadable PDF of worksheets and recipes from the book